DESAIN ANIMASI 2D SEBAGAI MEDIA PEMBELAJARAN ANAK USIA DINI DENGAN CERITA “AYAM DAN IKAN TONGKOL” - Raden Kusuma Candra Gusti Aji; Ahmad Khoirul Anwar; Yudi Wibowo (Canthing, 2024)
Animation is an image/object that is arranged in a regular manner that will be manipulated and will be arranged within a specified time so that it will make the image/object appear to be moving. At an early age, children cannot learn too hard, so they need a learning method in the form of games. Children are playing while learning. Children prefer learning through animation media. This combination of animation and comics aims to give children a new impression of animation. Moreover, it also aims to train children's reading levels at an early age. The design method used qualitative by collecting data directly through observing children's conditions in the environment, the internet and social media. As a result, this 2D animation was created using comic elements so it creates a new experience for young children and makes children learn through animation. Keywords: Animation, Early Age, Learning